SARS-CoV-2 Infection Induces Psoriatic Arthritis Flares and Enthesis Resident Plasmacytoid Dendritic Cell Type-1 Interferon Inhibition by JAK Antagonism Offer Novel Spondyloarthritis Pathogenesis Insights - Zhou, Qiao; Vadakekolathu, Jayakumar; Watad, Abdulla; Sharif, Kassem; Russell, Tobias; Rowe, Hannah; Khan, Almas; Millner, Peter A.; Loughenbury, Peter; Rao, Abhay; Dunsmuir, Robert; Timothy, Jake; et al. (Frontiers in Immunology, 2021)
Objective Bacterial and viral infectious triggers are linked to spondyloarthritis (SpA) including psoriatic arthritis (PsA) development, likely via dendritic cell activation. We investigated spinal entheseal plasmacytoid dendritic cells (pDCs) toll-like receptor (TLR)-7 and 9 activation and therapeutic modulation, including JAK inhibition. We also investigated if COVID-19 infection, a potent TLR-7 stimulator triggered PsA flares. Methods Normal entheseal pDCs were characterized and stimulated with imiquimod and CpG oligodeoxynucleotides (ODN) to evaluate TNF and IFNα production. NanoString gene expression assay of total pDCs RNA was performed pre- and post- ODN stimulation. Pharmacological inhibition of induced IFNα protein was performed with Tofacitinib and PDE4 inhibition. The impact of SARS-CoV2 viral infection on PsA flares was evaluated. Results CD45+HLA-DR+CD123+CD303+CD11c- entheseal pDCs were more numerous than blood pDCs (1.9 ± 0.8% vs 0.2 ± 0.07% of CD45+ cells, p=0.008) and showed inducible IFNα and TNF protein following ODN/imiquimod stimulation and were the sole entheseal IFNα producers. NanoString data identified 11 significantly upregulated differentially expressed genes (DEGs) including TNF in stimulated pDCs. Canonical pathway analysis revealed activation of dendritic cell maturation, NF-κB signaling, toll-like receptor signaling and JAK/STAT signaling pathways following ODN stimulation. Both tofacitinib and PDE4i strongly attenuated ODN induced IFNα. DAPSA scores elevations occurred in 18 PsA cases with SARS-CoV2 infection (9.7 ± 4 pre-infection and 35.3 ± 7.5 during infection). Conclusion Entheseal pDCs link microbes to TNF/IFNα production. SARS-CoV-2 infection is associated with PsA Flares and JAK inhibition suppressed activated entheseal plasmacytoid dendritic Type-1 interferon responses as pointers towards a novel mechanism of PsA and SpA-related arthropathy.